2004
DOI: 10.1093/geronb/59.5.s251
|View full text |Cite
|
Sign up to set email alerts
|

Volunteerism and Socioemotional Selectivity in Later Life

Abstract: Socioemotional selectivity theory is applicable to voluntary activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 30 publications
1
46
0
3
Order By: Relevance
“…Some research sought to make sense of the lower rates of volunteerism among older adults by exploring the way in which expectations, opportunities, and capabilities that shape whether and how much people engage in such activities change as people age. Hendricks and Cutler (2004) suggested that volunteerism trends may be explained by socio-emotional selectivity, and that volunteerism in later life appears to be related to changing needs, values, and capabilities as one ages. Similar research has recognized that the timing of life events (e.g., Musick et al 1999), and movement through life course transitions (e.g., Rotolo 2000) shape the forms and rates of voluntary participation because individuals have different incentives for volunteering during different periods of life.…”
mentioning
confidence: 99%
“…Some research sought to make sense of the lower rates of volunteerism among older adults by exploring the way in which expectations, opportunities, and capabilities that shape whether and how much people engage in such activities change as people age. Hendricks and Cutler (2004) suggested that volunteerism trends may be explained by socio-emotional selectivity, and that volunteerism in later life appears to be related to changing needs, values, and capabilities as one ages. Similar research has recognized that the timing of life events (e.g., Musick et al 1999), and movement through life course transitions (e.g., Rotolo 2000) shape the forms and rates of voluntary participation because individuals have different incentives for volunteering during different periods of life.…”
mentioning
confidence: 99%
“…Among these factors, the type of organization in which the older adult is involved appeared to be one of the most critical. This is because different organizations could attract volunteers with specific profiles (age, genre, motivations, for example) (Hendricks & Cutler, 2004;Penner, 2002). However, studies comparing volunteers gathered from different organizations have been scarce so far, and their results have not always been converging.…”
mentioning
confidence: 99%
“…Hasta el momento son numerosos los estudios que profundizan en los efectos del voluntariado sobre el bienestar de las personas mayores y sobre su salud mental y física (Musick, Herzog & House, 1999;Luoh & Herzog, 2002;Morrow-Howell, Hinterlong, Rozario & Tang, 2003;Lum & Lightfoot, 2005;Hao, 2008;Morrow-Howell, Hong & Tang, 2009;Ho, You & Fung, 2012). Las investigaciones realizadas no sólo han podido demostrar los efectos positivos del voluntariado sobre las tasas de mortalidad y la calidad de vida entre los mayores, sino también sobre otros aspectos socioemocionales como el sentimiento personal de logro, el compromiso emocional y la socialización de estas personas, lo que les ayuda a contrarrestarlas pérdidas de todo tipo que inevitablemente ocurren a su edad (Hendricks & Cutler, 2004).…”
Section: Voluntariado Mayores Y Valoresunclassified